Marketing Communication Strategies of Coffee Shops in Increasing Brand Awareness: A Qualitative Descriptive Study of Thousandsunnycoffee - Hidayat, Rahmad; Hidayat, Ofi (Universitas Muhammadiyah Mataram, 2024)
AbstractThis research aims to describe Thousandsunnycoffee's marketing communication strategy in an effort to increase consumer brand awareness of Thousandsunnycoffee coffee shops. The method used is descriptive qualitative with a focus on case studies. Data collected through in-depth interviews with coffee shop owners, baristas and consumers. Then make direct observations of the activities that occur in the Thousandsunnycoffee coffee shop, analyze the data that has been collected by interview and observation and then processed through a marketing communication strategy by determining marketing objectives, targeting, differentiation and positioning and also using the 4P marketing mix such as product, price, place and promotion. Also reinforced by using a promotional mix such as advertising, sales promotion, public relations, personal selling and direct marketing. Then by using brand awareness indicators to determine the brand awareness of Thousandsunnycoffee consumers. The results of the research obtained are that Thousandsunnycoffee successfully uses all aspects of the marketing communication strategy from the 4P marketing mix and the promotion mix and also all consumers are able to / know the existence of this brand from Thousandsunnycoffee. Some of the efforts made by Thousandsunnycoffee in carrying out marketing communication strategies include using social media, disseminating information about Thousandsunnycoffee to the public, holding promos that benefit consumers, collaborating in sports and sponsoring sports events.